Roles of Emotion in Negotiation Process: An Application of Drama Theory in Citarum Riverbasin Problem - Putro, Utomo Sarjono; Mangkusubroto, Kuntoro; Ariyanto, Khrisna (SBM ITB, 2008)
Citarum was a clean river which local people enjoyed fishing and recreation, however now its condition has already changed totally. Currently, the river can not provide its social services, such as clean water, electricity, fishing, tourisms, transportation, and public recreation. In rainy season, the color of river is brown because it contains mud from bald lands erosion along the river. In dry season, the color of river has changed to black and full of household wastes. In spite of many seminars were held, classical problems always arise. There are floods in rainy season but changes drastically to drought in dry season. There are some factors which cause the problem, i.e. illegal lodging and the population exploading in upper stream, population from industries in down stream, etc. this paper tries to see the Citarum problem from a different point of view, and starts from the belief that if stakeholders (or agents) in the Citarum problem collaborate to solve the problem, then Citarum river will be better and better. This paper analyzes negotiation process among the agents, and tries to describe how the negotiation process can end with collaboration. In the first step, drama theory framework is applied to model the negotiation process. Then, we simulate model by using SOARS (Spot Oriented Agent Role Similator). Finally, simulation results show that emotion of agents has important role to encourage collaboration; that is, the more the agents who have positive emotion (or tend to compromise), the less the number of impediments (or dilemma) to achieve collaboration.Â Keywords: quality policy, Institut Teknologi Bandung (ITB), higher education